A review of sustainable development in the Chilean mining sector: past, present and future. Issue 2 (17th February 2017) - Ghorbani, Yousef; Kuan, Seng How
Abstract: Chile is the principal producer of copper with a total of 5.8 million tonnes fine copper production in 2013. Chilean mining industry currently faces a projected increase in waste production, depleting water resources in the arid mining regions of the north and a lack of fossil fuel energy sources. In this study, a review of the historical background of environmental practices in Chile is presented, focused between 1970 and 2010. A review of the current state of sustainable development, comprising energy, water, stakeholder participation, environmental impacts and institutional decentralisation in the mining industry is presented.